2022
DOI: 10.3390/toxins14110723
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Proteomic Profiling of African Viperidae and Elapidae Snake Venoms and Their Antivenom Neutralisation

Abstract: Snakebite envenoming is a neglected tropical disease (NTD) that results from the injection of snake venom of a venomous snake into animals and humans. In Africa (mainly in sub-Saharan Africa), over 100,000 envenomings and over 10,000 deaths per annum from snakebite have been reported. Difficulties in snakebite prevention and antivenom treatment are believed to result from a lack of epidemiological data and underestimated figures on snakebite envenoming-related morbidity and mortality. There are species- and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 122 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…This is well exemplified by previous immunoprofiling studies applying microarrays ( Engmark et al, 2016 ) and enzyme-linked immunosorbent assay ( Lingam et al, 2020 ), as well as in vivo neutralization studies that showed viperid antivenoms are significantly more potent than elapid antivenoms ( Calvete et al, 2016 ; Ratanabanangkoon et al, 2016 ; Bailon Calderon et al, 2020 ; Faisal et al, 2021 ). This is likely due to most viperid venoms are predominated with high MW toxins (MW > 25 kDa) (e.g., SVMP and snake venom serine protease, SVSP) ( Offor et al, 2022 ), which are capable of eliciting stronger immune response for the production of neutralizing antibodies. However, given that venoms constituting neurotoxins of more than ∼40% failed to raise antivenoms with major improvement in neutralization efficacy ( Tan et al, 2015b ; Tan et al, 2016a ; Tan et al, 2019a ; Palasuberniam et al, 2021 ), it is therefore suggested that the low neutralizing efficacy of elapid antivenom may be also attributed to other factors, such as amino acid composition, that intrinsically modulate the epitope configuration of α-NTXs to be recognized by T-cell receptor (TCR) to elicit a strong humoral response.…”
Section: Resultsmentioning
confidence: 99%
“…This is well exemplified by previous immunoprofiling studies applying microarrays ( Engmark et al, 2016 ) and enzyme-linked immunosorbent assay ( Lingam et al, 2020 ), as well as in vivo neutralization studies that showed viperid antivenoms are significantly more potent than elapid antivenoms ( Calvete et al, 2016 ; Ratanabanangkoon et al, 2016 ; Bailon Calderon et al, 2020 ; Faisal et al, 2021 ). This is likely due to most viperid venoms are predominated with high MW toxins (MW > 25 kDa) (e.g., SVMP and snake venom serine protease, SVSP) ( Offor et al, 2022 ), which are capable of eliciting stronger immune response for the production of neutralizing antibodies. However, given that venoms constituting neurotoxins of more than ∼40% failed to raise antivenoms with major improvement in neutralization efficacy ( Tan et al, 2015b ; Tan et al, 2016a ; Tan et al, 2019a ; Palasuberniam et al, 2021 ), it is therefore suggested that the low neutralizing efficacy of elapid antivenom may be also attributed to other factors, such as amino acid composition, that intrinsically modulate the epitope configuration of α-NTXs to be recognized by T-cell receptor (TCR) to elicit a strong humoral response.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, crotoxin PLA 2 is the only snake venom toxin that has shown promise through phase I clini- to enhance its efficacy, pharmacokinetics and pharmacodynamics as demonstrated in the production of cardiovascular drugs Enalapril (Faisal et al, 2021). Since inter-and intra-specific variations have also been reported in African snake venom toxins (Offor et al, 2022), it can be beneficial to also explore more anticancer testings with the snakes endemic within the continent.…”
Section: Discussionmentioning
confidence: 99%
“…These toxins can be short-chain, long-chain or non-conventional and are dominant in the venom of elapids (Kini & Doley, 2010;Offor et al, 2022). Table 5 shows the anticancer activities of 3FTxs from snake venoms.…”
Section: Three-finger Toxin Anticancer Activitiesmentioning
confidence: 99%
See 2 more Smart Citations